2012
DOI: 10.1007/s12291-012-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Are hsCRP Levels and LDL/HDL Ratio Better and Early Markers to Unmask Onset of Dyslipidemia and Inflammation in Asymptomatic Subclinical Hypothyroidism?

Abstract: The implications of subclinical hypothyroidism (SCH) are many amongst which the most important is progression to overt hypothyroidism. Other debatable aspects are its association with cardiovascular risk, neuromuscular and psychiatric dysfunction, increased predisposition to developing metabolic syndrome and an underlying pro-inflammatory state. We aimed to study the lipid profile, lipoprotein(a) [Lp(a)] and hsCRP levels and insulin resistance in a group of patients with SCH in a referral hospital and see if a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…However, previous studies have shown no changes in both FT3 and FT4 after 12 weeks of MMT, but our findings showed drop in values after 12 months. In our study too, we found out some decrease in FT3 after 6 months compared to diagnosis, but the decrease in values are not statistically significant [15,22]. FT4, one of the important thyroid hormones which are usually done along with TSH, all values were found to be perfectly normal, but at the lower MMT, but our study did not find such effects.…”
Section: Liver Function Testscontrasting
confidence: 44%
See 2 more Smart Citations
“…However, previous studies have shown no changes in both FT3 and FT4 after 12 weeks of MMT, but our findings showed drop in values after 12 months. In our study too, we found out some decrease in FT3 after 6 months compared to diagnosis, but the decrease in values are not statistically significant [15,22]. FT4, one of the important thyroid hormones which are usually done along with TSH, all values were found to be perfectly normal, but at the lower MMT, but our study did not find such effects.…”
Section: Liver Function Testscontrasting
confidence: 44%
“…No significant was found between LP(a) and IR. Hence, LDL-c/HDL-c ratio may be useful in the diagnosis of SCH [15].…”
Section: Kumar Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] Positive correlation of CRP with serum TSH (r= 0.626, P=0.0001) is a worth findings supported by previous studies. [29][30][31] Association of CRP with dyslipidemia has been reported previously [32][33][34] in SCH patients. A previous study 33 reported increased risk of atherosclerotic vascular disease in SCH patients as indicated by dyslipidemia and hsCRP.…”
Section: Discussionmentioning
confidence: 90%
“…Mahto M et al study stated that the elevated LDL-cholesterol/HDL-cholesterol ratio can highlight the cardiac risk and have the potential to become a part of the screening process of SCH patients along with CRP to detect the cardiovascular abnormality. 29 CHOD-POD method, GPO-PAP method and CHOD-POD/Phosphotungstate method respectively. Erba Chem, Germany kits were used for the estimation of lipid parameters.…”
Section: Methodsmentioning
confidence: 99%